The Role of Social Media In Public Health Communication And Behavior Change In Adolescents - ALAQIL, RAYANA ABDULQANI; alaqeel, Ryouf abdulgni; alhawiti, Reem dahi; alhawiti, Ayed eid; Aljizani, Wafaa frug Amin; Alatawi, Dalal mutlaq Amer; alatwi, Gamela atallah; Albalawi, Waad Eid Salamah; aljofi, homoud saleh; alshammari, majed basheer; almsodaia, mosa sulimaen; alatwi, saud salman; et al. (Journal of Posthumanism, 2024)
This study demonstrated that social media plays a significant role in shaping health communication and influencing behavior among adolescents. While platforms like Instagram and TikTok provide valuable avenues for promoting awareness— particularly around mental health and nutrition—concerns about misinformation and uneven behavior change remain. Collaborations between health authorities and trusted influencers, along with improved digital literacy, are essential for maximizing benefits and minimizing risks in adolescent public health communication.